Analysis of the Influence of Submarine Operational Capabilities on the State of Deterrence - Timbul Haryanto AR; A. Octavian; Romie O. Bura (Publikasi Indonesia, 2022)
Indonesia is an archipelagic state whose territory lies in a cross position between two continents and two oceans. So that Indonesia has the authority to maintain the security of its maritime territory, starting from regulating its shipping lanes to maintaining sovereignty in all of Indonesia's sea areas. Indonesia's threats have been identified as coming from neighboring countries, namely Malaysia, Singapore, Thailand, and China. Increasing escalation in the South China Sea area, Efforts to support Indonesian territorial security, submarines currently owned must be able to become a deterrent against potential threats both from within and from outside and be able to operate in all Indonesian waters. The hypothesis in this study is if the operational capability of the submarine increases the country's deterrence system. The methodology used is descriptive quantitative using software SPSS 25 and Microsoft Excel 2013 with data analysis techniques using multivariate correlation. The effect of submarine operational capability on the country's deterrence is 86.6% that implies submarine operational capability has strong influence.